2018
DOI: 10.1021/acs.nanolett.8b03508
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Gated Two-Layer Silicon Nanowire FETs: Evidence of Controlling Single-Trap Dynamic Processes

Abstract: We fabricate two-layer (TL) silicon nanowires (NW) field-effect transistors (FETs) with a liquid gate. The NW devices show advanced characteristics, which reflect reliable single-electron phenomena. A strong modulation effect of channel conductivity with effectively tuned parameters is revealed. The effect opens up prospects for applications in several research fields including bioelectronics and sensing applications. Our results shed light on the nature of single trap dynamics which parameters can be fine-tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…Therefore, noise in such devices has attracted a considerable attention mainly as a limiting factor for sensors performance. However, it was recently demonstrated that the low‐frequency noise in nanotransistor‐based biosensors can be successfully used as a useful signal . In particular, it has been shown that biosensors based on liquid‐gated nanowire FETs can demonstrate the random‐telegraph noise caused by the single trap phenomena .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, noise in such devices has attracted a considerable attention mainly as a limiting factor for sensors performance. However, it was recently demonstrated that the low‐frequency noise in nanotransistor‐based biosensors can be successfully used as a useful signal . In particular, it has been shown that biosensors based on liquid‐gated nanowire FETs can demonstrate the random‐telegraph noise caused by the single trap phenomena .…”
Section: Introductionmentioning
confidence: 99%
“…However, it was recently demonstrated that the low‐frequency noise in nanotransistor‐based biosensors can be successfully used as a useful signal . In particular, it has been shown that biosensors based on liquid‐gated nanowire FETs can demonstrate the random‐telegraph noise caused by the single trap phenomena . In this specific case, improved sensitivity to the analyte can be obtained by considering trapping‐detrapping noise as a useful signal .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations